Climate policies and Sweden's green industrial revolution - Pareliussen, Jon (OECD Publishing, 2023)
Sweden is among OECD best performers in reducing greenhouse gas emissions, much thanks to a comprehensive policy framework and relatively efficient policies. There is nonetheless room to further improve consistency of targets and policies, notably for transport, agriculture and carbon removals. Sweden's long record as a climate frontrunner is also threatened by policy changes moving the 2030 reduction target out of reach unless compensated by new ambitious measures. A green industrial revolution is gaining momentum in Sweden's north, fuelled by an abundant supply of clean electricity. Considerable investments in electricity generation, storage and transmission are needed, but long planning and permitting procedures slow many key projects down. The green revolution depends on people and skills to run industry and complementary public services. This is a challenge for northern regions and municipalities already facing labour shortages
Keywords: Economics; Sweden